COVID-19 vaccine knowledge, attitudes, perceptions and uptake among healthcare workers of Pune district, Maharashtra - Shalini Bassi; Deepika Bahl; Nishibha Thapliyal; Heeya Maity; Saddicha Dilip Marathe; Bhrunal Bajarang Prakshale; Vinod Gajanan Shah; Subhash R. Salunke; Monika Arora (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Healthcare workers play a vital role in vaccine promotion and acceptance through community dialogue, education, and myth-busting. Vaccinated healthcare workers will likely recommend the vaccine to their families and community. # Methods A cross-sectional study was conducted with healthcare workers (n=357) to understand their knowledge, attitudes, perceptions, and acceptance of the coronavirus disease 2019 (COVID-19) vaccine. The study was conducted in two blocks (Haveli and Velhe) of Pune, Maharashtra. # Results The findings showed that over 90% of healthcare workers knew about COVID-19 vaccination and had a positive attitude towards COVID-19 vaccination. Among them, vaccine uptake was high (93% with two doses and 4% with a single dose). 98% of healthcare workers believed that vaccine is safe to use. However, few gaps existed around vaccine safety, side effects and allergic reactions, as 27.7% believed that the COVID-19 vaccine could increase the risk of allergic reactions, 51.8% believed that acquiring natural immunity by contacting the virus is better than vaccination, 16.5% believed that it is possible to reduce the incidence of COVID-19 without vaccination, 28.9% believed that vaccine might have side effects and 14% believed vaccine is not the most likely way to control the pandemic. # Conclusions Addressing the existing gaps and reinforcing the relevance of the COVID-19 vaccine through a structured program is critical to empower health workers to disseminate accurate information to the community, consecutively improve vaccination uptake, and boost vaccination efforts in India.